Militant competition: how terrorists and insurgents advertise with violence and how they can be stopped - Conrad, Justin (Cambridge University Press, 2021)
Militant groups often use violence, perversely, to gain attention and resources. In this book, the authors analyze how terrorist and rebel organizations compete with one another to secure funding and supporters. The authors develop a strategic model of competitive violence among militant groups and test the model's implications with statistical analysis and case studies. A series of model extensions allow the authors to incorporate the full range of strategic actors, focusing in particular on government efforts to counter and deter violence. The results indicate that the direct effects of competition are not as clear as they may seem, and interventions to alter competitive incentives may backfire if states are not careful. This is a timely contribution to a growing body of political economy research on militant group fragmentation, rivalry, fratricide and demonstrative violence.